Mid-Level Riverine Outflow Matters: A Case of Microplastic Transport in the Jiulong River, China - Li, Yifan; Liu, Siguang; Liu, Mengyang; Huang, Wei; Chen, Kai; Ding, Yongcheng; Wu, Fangzhu; Ke, Hongwei; Lou, Linghao; Lin, Yan; Zhang, Mingyu; Liu, Fengjiao; et al. (Frontiers in Marine Science, 2021)
Riverine outflow is one of the major pathways for microplastic transportation to coastal environments. Research on the output of microplastics in small- or medium-sized rivers will help accurately understand the status of their marine loads. In this study, we used both trawling and pumping methods to collect microplastics of different sizes in the Jiulong River Estuary and Xiamen Bay. We found that the abundance of small microplastics (44 μm–5.0 mm) was at least 20 times higher than the large particles (0.33–5.0 mm). The abundance of the large particles ranges from 4.96 to 16.3 particles/m3, and that of the small particles ranged from 82.8 to 918 particles/m3. Granule was the dominant shape (>60%), and polyethylene (PE), polypropylene (PP), and polyethylene terephthalate (PET) were the most common components. The riverine flux of small microplastics (44 μm–5 mm, 472 ± 230 t/y) was at a medium level and was eight times greater than that of large particles (0.33–5.0 mm, 61.2 ± 2.6 t/y). The behavior of the large microplastics was relatively conservative, whose abundance had a significant correlation with salinity (R2 = 0.927) and was mainly influenced by physical factors. In contrast, results of statistical analysis revealed that more complicated factors influenced the small microplastics.